AN ANALYSIS OF STUDENTS’ PROBLEMS IN SPEAKING ACTIVITY AT SMAN 1 NARMADA - Rahmad Ramdani; Muhamad Suhaili; Sudirman (Sinar Lima, 2026)
This study investigated the problems encountered by students in English speaking activities at SMAN 1 Narmada. The research aimed to identify the major speaking problems experienced by students and to explore the factors contributing to those difficulties during classroom speaking activities. A qualitative descriptive research design was employed in this study. The participants consisted of tenth-grade students of SMAN 1 Narmada selected through purposive sampling, along with the English teacher as a supporting informant. Data were collected through classroom observations, oral speaking tests, semi-structured interviews, questionnaires, and documentation, and were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing and verification. The findings revealed that students experienced six major problems in speaking activities, namely limited vocabulary, poor pronunciation, lack of confidence, fear of making mistakes, limited grammar mastery, and low fluency. Among these problems, limited vocabulary and lack of confidence emerged as the most dominant factors affecting students' speaking performance. The findings also showed that students' speaking difficulties were influenced by both linguistic factors, including vocabulary, pronunciation, grammar, and fluency, and psychological factors, such as speaking anxiety and low self-confidence. Overall, the findings indicate that improving students' speaking competence requires more communicative teaching practices, regular opportunities for speaking practice, and a supportive classroom environment that encourages students to communicate confidently in English.